Phenotypic and functional characteristics of monocyte subsets in the blood and bone marrow of Indian subjects with Visceral Leishmaniasis. - Gulafsha Kausar; Shashi Bhushan Chauhan; Ritirupa Roy; Vimal Verma; Sundaram Pandey; Aziza Niyaz; Jaya Chakravarty; Christian R Engwerda; Susanne Nylen; Rajiv Kumar; Mary E Wilson; Shyam Sundar (Public Library of Science (PLoS), 2024)
Visceral leishmaniasis (VL) is a potentially fatal parasitic infection caused by Leishmania donovani in India. L. donovani is an obligate intracellular protozoan residing mostly in macrophages of the reticuloendothelial system throughout chronic infection. Monocytic phagocytes are critical in the pathogenesis of different forms of leishmaniasis. Subsets of monocytes are distinguished by their surface markers into CD14+CD16- classical monocytes, CD14+CD16+ intermediate monocytes, and CD16++CD14low non-classical monocyte subsets. During cutaneous leishmaniasis (CL), intermediate monocyte are reported to be a source of inflammatory cytokines IL-1β and TNF, and they express CCR2 attracting them to sites of inflammatory pathology. We examined monocyte subsets in the blood and bone marrow of patients with VL from an endemic site in Bihar, India, and found these contrasted with the roles of monocytes in CL. During VL, intermediate and non-classical CD16+ monocyte subsets expressed instead a non-inflammatory phenotype with low CCR2, high CX3CR1 and low microbicidal oxidant generation, making them more similar to patrolling monocytes than inflammatory cells. Bone marrow CD16+ monocyte subsets expressed a phenotype that might be more similar to the inflammatory subsets of CL, although our inability to obtain bone marrow from healthy donors in the endemic region hampered this interpretation Overall the data suggest that CD16+ intermediate monocyte subsets in VL patients express a phenotypes that contributes to an immunosuppressed pathologic immune state, but in contrast to CL, these do not mediate localized inflammatory responses.